Kavrulan Tütünden Oluşan Gazların Bazı Maddeler Üzerinde Adsorpsiyonu ve Desorpsiyonu - YALÇINKAYA, Zeki; CEYLAN, Hasan (MAS Journal of Applied Sciences, 2022)
In this study, some vapor phase components formed during the tobacco roasting-process wereidentified by gas chromatography. Of the tobacco samples studied, the amounts of nicotine and benzylalcohol were the highest. Volatiles occurring at 100C were generally less than those formed at 150C. Itwas observed that the amount of volatiles in Bitlis Sirmaçek Village tobacco was slightly higher than MuşAhçivan tobacco roasted at the same temperature. Adsorption on alumina, sepiolite and silica gel anddesorption of adsorbed components by diethyl ether extraction were investigated in order to recover volatilesubstances that can be used as cigarette flavorings from tobacco roasting. The adsorption and desorptionactivities of nicotine, 5-methylfurfural, acetol and pyridine, which are the main components in the vaporphase formed by the tobacco roasting process, were investigated. In addition, the components adsorbed onsilica gel were recovered by an organic solvent extraction method. Recovery by carbon disulfide extractionshowed maximum efficiency and many volatile compounds, especially sugar-like thermal decompositionproducts, were recovered in good yield. Adsorption efficiencies of adsorbents are discussed with their rawmaterial, specific surface area, micropore size distribution and affinity of volatile components.